A content analysis on the quantity of violent acts of the fantasy shows Dyesebel and Dyosa - Getizo, Estella Mae R.
The relationship between the media violence and aggressive behavior has been a debate since the invention of the television. Scholars say that media violence is casually link to aggressive behavior while other scholars still don't adhere to this thought. Fantasy shows, like Dyesebel and Dyosa, in the country are believed to have greater number of audience than soap operas. Moreover, their audience usually ranged from 2-12 years old. A content analysis is done to identify the amount of violent acts that theses shows portrayed. The prevalence of violent acts as well as who usually conducts, to whom, in what manner, and why were also evaluated in this study. Dyosa portrayed more violent acts than Dyesebel during their respective data gathering period. However, Dyesebel portrayed more physical violence (done by bare hands and used of weapons like knives, guns, etc.) than acts that used magic. Also, in the National Urban TV Audience Measurement (NUTAM) survey as of October 2008 by AGB Nielsen, Dyesebel had more audience that range from 1-12. Different mass media theories were used to analyze the results gathered and its possible relationship with aggressive behavior.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts